The Psychological Profile Of The Cyber Criminal A Study Of His Psychological Features - نوار شهرزاد (مجلة دراسات في سيكولوجية الانحراف, 2021)
In recent years, the world has known a significant rise and a new type of crime, what is called cybercrime or electronic crime resulting from the poor use of informatics, targeting individuals, institutions and countries. Cybercrime is a kind of information fraud and a "deliberate intention of a harmful or socially attended act" that has contributed to the increase prevalence of urbanization, self-assertion, and the desire for rapid profit. However, we note that most studies have already taken care of criminality (cybercrime), but have neglected the psychological characteristics of its perpetrators and the motives for fraud and manipulation, .Basing on that, the current study attempts to address the psychological dimensions of the cybercriminal by recognizing the psychological features of his personality.